A Potential Therapeutic Strategy for Malignant Mesothelioma with Gene Medicine. (16th January 2013) - Tada, Yuji; Shimada, Hideaki; Hiroshima, Kenzo; Tagawa, Masatoshi
Abstract : Malignant mesothelioma, closely linked with occupational asbestos exposure, is relatively rare in the frequency, but the patient numbers are going to increase in the next few decades all over the world. The current treatment modalities are not effective in terms of the overall survival and the quality of life. Mesothelioma mainly develops in the thoracic cavity and infrequently metastasizes to extrapleural organs. A local treatment can thereby be beneficial to the patients, and gene therapy with an intrapleural administration of vectors is one of the potential therapeutics. Preclinical studies demonstrated the efficacy of gene medicine for mesothelioma, and clinical trials with adenovirus vectors showed the safety of an intrapleural injection and a possible involvement of antitumor immune responses. Nevertheless, low transduction efficiency remains the main hurdle that hinders further clinical applications. Moreover, rapid generation of antivector antibody also inhibits transgene expressions. In this paper, we review the current status of preclinical and clinical gene therapy for malignant mesothelioma and discuss potential clinical directions of gene medicine in terms of a combinatory use with anticancer agents and with immunotherapy.